Clinical outcomes for patients after surgery and radiation therapy for mesenchymal chondrosarcomas. Issue 8 (28th October 2016) - De Amorim Bernstein, Karen; Liebsch, Norbert; Chen, Yen‐Lin; Niemierko, Andrzej; Schwab, Joseph H.; Raskin, Kevin; Lozano‐Calderon, Santiago A.; Cote, Gregory; Harmon, David C.; Choy, Edwin; Haynes, Alex; Mullen, John; et al.
Abstract : Introduction: We report the outcome of 23 patients with mesenchymal chondrosarcomas treated with surgery and radiation therapy +/− chemotherapy. The intent of the project was to review the impact of patient and treatment variables on treatment outcome, in particular with regard to extent of surgery and radiation dose. Patients and Methods: Twenty‐three patients with mesenchymal chondrosarcomas were treated with surgery and radiation therapy (min. dose 44 Gy; max. dose 78 Gy; median dose 60 Gy; mean dose 61 Gy). Results: The median survival for the entire cohort of patients was 21.65 years (95% confidence interval ± 4.25). The 5‐ and 10‐year OS was 78.6%. Median disease‐free survival for the 23 patients was 7.2 years. Disease‐free survival (DFS) at 3 and 5 years was 70.7% and 57.8%, respectively. The local control rate at 5 and 10 years was 89.5% (95%CI 64.1–97.3%). Only three patients experienced local failure, three patients had regional failure, and eight developed distant metastases. Conclusions: In this cohort of patients local tumor control was high when using a combination of surgery and radiation. There was not a clear relationship between radiation dose and local tumor control. J. Surg. Oncol. 2016;114:982–986 . © 2016 Wiley Periodicals, Inc.